Religious identities and the struggle for secularism: the revival of buddhism and religions of marginalized groups in Nepal - Torri, Davide (Entangled Religions, 2019)
One of the most relevant aspects of contemporary political life in Nepal is the rise of ethnic minorities. From the early 1990s, the movement for democracy started campaigning against Hindu Monarchic autocracy for the lifting of the ban on political parties, the recognition of multiculturalism and freedom of religion. Many things have changed since then: a Maoist-led insurgency and a new people's movement have managed to topple the monarchy and to transform the Himalayan country into a republic. As a reaction to the state-enforced Hinduization of the people, supporting the caste system and maintaining the power in the hands of high caste Hindus, many groups are now campaigning to revive their local cultures and traditions. Religion is one of the key areas of confrontation, and the struggle for secularism has created space for the revival of the religious traditions of marginalized groups.